GAMBARAN RHEUMATOID FACTOR PADA LANJUT USIA DI WILAYAH KERJA PUSKESMAS TOTO UTARA - nurmila domut; Adnan Malaha; Adnan Engelen (Journal of Health, Technology and Science (JHTS), 2021)
Rheumatoid factor (RF) is an immunoglobulin that reacts with the IgG molecule as its name indicates, RF is primarily used for the examination and monitoring of rheumatoid arthritis. Rheumatoid arthritis (rheumatism) is a disease where the immune system fails to distinguish its own tissue from foreign substances. The aim of the study was to determine the results of rheumatoid factor in the elderly in the working area of ​​the Toto Utara Public Health Center, Bone Bolango Regency, Gorontalo Province. The method used in this study is a descriptive qualitative approach, with primary data sources in the form of examination resultsrheumatoid factorin the serum of patients with rheumatoid arthritis in a number of 15 samplesobtained using the sampling technique that ispurposive sampling. The results of the examination of rheumatoid factor using serum obtained inOf the 15 samples of rheumatoid arthritis sufferers aged 60 to 63 years who were positive by examining the agglutination test using the glory diagnostic kit test tool, on the results of laboratory tests, there were 4 samples (26.6%) positive for rheumatoid factor, namely 3 were female (20%) and 1 was male. male sex (6.6%).